Multimedia Center Design In Banda Aceh with High-Tech Architecture Approach - Nafis, Badratul; Joni, Muhammad; Marlina, Henny (Rumoh Journal of Architecture, 2023)
Multimedia serves as a medium for conveying information through the integration of various elements, including text, sound, images, animation, audio, and video. In Banda Aceh, formal media institutions—such as TVRI Aceh, RRI Banda Aceh, and Baiturrahman FM—alongside creative communities like the Aceh Film Community and Aceh Animation Community, operate independently. This fragmentation highlights the need for an integrated hub capable of unifying content production, distribution, and public dissemination of local multimedia. This study proposes the design of a Multimedia Center in Banda Aceh as a response to this need. The building adopts a High-Tech architectural approach, emphasizing transparency, layering, and movement—expressed through tempered low-e glass façades, intelligent building skins, and transparent elevators that convey dynamism. The structural system utilizes lightweight vertical steel frameworks as expressive architectural elements. Located on Jalan Cut Meutia, Kecamatan Baiturrahman, the center occupies a 17,798 m² site, with a building footprint (KDB) of 14,231 m² and a total floor area (KLB) of 80,091 m². Designed as a five-story, single-mass public building (Class 9), it accommodates three primary functional zones: management (director’s office, deputy director, secretariat), multimedia production (news broadcasting studio, Aceh News TV station, animation studio, digital video and filming studios), and public amenities (auditorium, multimedia library, food court, ATM center, and more). The Multimedia Center is envisioned as a dynamic hub for creating, sharing, and celebrating Aceh’s unique cultural and informational content.